PENGELOLAAN PIUTANG SIMPAN PINJAM PADA KOPERASI HIDAYAH SAMARINDA - Tobing, Vina Agustina (EKONOMIA, 2014)
Hidayah Cooperative is a cooperative whose main activity was to accept deposits from members, and channel them back to members who need a loan to open up and increase its business in the form of short-term credit. Cooperative Hidayah established only four years, during the four years of the establishment of the system used is still very simple and has several drawbacks. in order to manage the accounts properly will require adequate internal controls, in order to assess the suitability of the implementation of the standards and established procedures, and tools that can be used to ensure the appropriateness and effectiveness of operational activities support the realization of receivables management is an internal audit. Formulation of the problem in this study is